Modification of Financial Ratio Analysis Based on Fair Value: Is It More Predictive? - Nur Rahmanti Ratih; Marhaendra Kusuma; Yuniep Mujati Suaidah; Abdul Hadi Bin Ahamad (University of Merdeka Malang, 2025)
The purpose of this study is to respond to these profit changes by modifying the ROA, ROE, and NPM ratio formulas by expanding the concept of